Curricular environmentalization: an exploration in environmental awareness - Jiménez Gutiérrez, Yeymmy Paola; Cristancho Chinome, Jaime Ricardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
Curricular environmentalization represents a transversal pedagogic approach included in the curriculum, which is understood as a convergence of knowledge, experiences, objectives, and guiding factor upon methodological practices. It introduces a great challenge for educational authorities and the academic community in general. The present article reflects from literary bases supported by two axes: environmental and curricular centre, on how this process has been applied within the curriculum and taking as a reference the research proposal made by Parga (2013) under steps of curricular design proposed by (Taba, 1974) in the national reality. Finally, considerations are made emphasizing the urgent commitment that educational institutions must have in the construction, planning, and execution of an environmentalized and contextualized curriculum.